HASIL TANAMAN JAGUNG MANIS (Zea mays saccharata L.) PADA BEBERAPA DOSIS PUPUK ORGANIK - Polii, Meity G.M.; Tumbelaka, Selvie (EUGENIA, 2012)
ABSTRACT   The study aimed to determine the effect of liquid organic fertilizer Super Aci application to the production of super sweet corn. Randomized group design with six fertilizer dosage treatments which are A= without fertilizer; B= N, P and K fertilizers with recommended dosages; C= organic liquid fertilizer Super Aci with 1 cc / liter of water dosage; D= organic liquid fertilizer Super Aci with 2 cc / liter of water dosage;  E = organic liquid fertilizer Super Aci with  3 cc / liter of water dosage;  and F = organic liquid fertilizer Super Aci with 4 cc / liter of water dosage. Observed variables include 1). Length of corn cob, measured at harvest; 2) corn cob diameter measured at harvest; corn cob weight measured at harvest. The data were analysed using analysis of variance and if the treatments were significantly difference then the analysis was continued with Least Significant Difference (LCD) of 5%. The results showed that the use of liquid organic fertilizer influenced the production of super sweet corn. The application of anorganic fertilizer N, P, and K also affected the growth and development of super sweet corn. The applicaton of organic fertilizer with 4 cc/water dosage gave the highest length and weight of the sweet corn. Key words: Organic fertilizer Super Aci, sweet corn crop ABSTRAK   Penelitian ini bertujuan untuk mengetahui pengaruh pemberian pupuk organik cair Super Aci terhadap hasil jagung manis. Penelitian menggunakan Rancangan Acak Kelompok terdiri dari enam perlakuan dosis pupuk, yaitu A = Tanpa pupuk, B = Pupuk an organik N,P, dan K dosis rekomendasi, C = Pupuk organik cair Super Aci dosis 1 cc / liter air, D = Pupuk organik cair Super Aci dosis 2 cc / liter air, E = Pupuk organik cair Super Aci dosis 3 cc / liter air, dan F = Pupuk organik cair Super Aci dosis 4 cc / liter air. Variabel yang diamati adalah 1) Panjang Tongkol, diukur pada saat panen, 2) Diameter tongkol, diukur pada saat panen, dan 3) Bobot Tongkol, ditimbang pada saat panen. Data dianalisis menggunakan analisis varians dan apabila terdapat pengaruh perlakuan dilanjutkan dengan uji BNT 5%. Hasil penelitian menunjukkan bahwa perlakuan pupuk organik cair Super Aci mempengaruhi hasil jagung manis. Pupuk an organik N,P, dan K serta pupuk organik cair Super Aci mempengaruhi hasil jagung manis dimana pupuk an organik N,P, dan K dosis rekomendasi serta pupuk organik cair Super Aci dosis 4 cc / liter air memberikan panjang dan bobot tongkol jagung manis tertinggi. Kata kunci : Pupuk organik Super Aci, tanaman jagung manis